Victor Rico-Gray (1951-2021): a journey through the life of a great visionary in ecology - Castillo Guevara, Citlalli; Cuautle, Mariana; Díaz-Castelazo, Cecilia; Serio Silva, Juan Carlos (Instituto de Ecología, A.C., 2023)
As a tribute and permanent memory of those of us who were his students, continuing his legacy, in commemoration of his death anniversary, on April 4.